An Intelligent Electronic Convergence Monitoring System for Underground Coal Mines - Hutchinson IN (The Australasian Institute of Mining and Metallurgy, 1991)
In order for the Australian underground coal mining industry to achieve the high productivity rates demanded of it without compromising its good safety record, improved geotechnical monitoring systems are required. One of the main problem areas affecting underground coal mining is the deterioration of previously stable roadways.CSIRO Division of Geomechanics has been working on a NERDDC funded project to develop an instrument to monitor coal mine roof deformation. The instrument which has been developed, Roof Alert, is a self contained, battery powered, intrinsically safe device. It can monitor the magnitude and rate of deformation and give multiple, variable visual alarm signals where preset levels ate exceeded.